Substrate interaction defects in histidyl‐tRNA synthetase linked to dominant axonal peripheral neuropathy. Issue 3 (26th December 2017) - Abbott, Jamie A.; Meyer‐Schuman, Rebecca; Lupo, Vincenzo; Feely, Shawna; Mademan, Inès; Oprescu, Stephanie N.; Griffin, Laurie B.; Alberti, M. Antonia; Casasnovas, Carlos; Aharoni, Sharon; Basel‐Vanagaite, Lina; Züchner, Stephan; et al.
Abstract: Histidyl‐tRNA synthetase (HARS) ligates histidine to cognate tRNA molecules, which is required for protein translation. Mutations in HARS cause the dominant axonal peripheral neuropathy Charcot‐Marie‐Tooth disease type 2W (CMT2W); however, the precise molecular mechanism remains undefined. Here, we investigated three HARS missense mutations associated with CMT2W (p.Tyr330Cys, p.Ser356Asn, and p.Val155Gly). The three mutations localize to the HARS catalytic domain and failed to complement deletion of the yeast ortholog ( HTS1 ). Enzyme kinetics, differential scanning fluorimetry (DSF), and analytical ultracentrifugation (AUC) were employed to assess the effect of these substitutions on primary aminoacylation function and overall dimeric structure. Notably, the p.Tyr330Cys, p.Ser356Asn, and p.Val155Gly HARS substitutions all led to reduced aminoacylation, providing a direct connection between CMT2W‐linked HARS mutations and loss of canonical ARS function. While DSF assays revealed that only one of the variants (p.Val155Gly) was less thermally stable relative to wild‐type, all three HARS mutants formed stable dimers, as measured by AUC. Our work represents the first biochemical analysis of CMT‐associated HARS mutations and underscores how loss of the primary aminoacylation function can contribute to disease pathology. Abstract : Disease‐causing variants in multiple aminoacyl‐tRNA synthetase genes have been linked to the dominant inherited peripheral neuropathy Charcot Marie Tooth (CMT) disease. Here, we employed yeast complementation, enzyme kinetics, differential scanning fluorimetry (DSF), and analytical ultra centrifugation (AUC) to investigate three histidyl‐tRNA synthetase (HARS) missense mutations associated with CMT2W (p.Tyr330Cys, p.Ser356Asn, and p.Val155Gly). The mutant substitutions all led to reduced catalytic activity and poorer histidine and ATP binding, illustrating how loss of primary aminoacylation function can contribute to disease pathology.